CHEMICAL COMPOSITION AND BIOLOGICAL EVALUATION OF HERACLEUM PASTINACIFOLIUM SUBSP. TRANSCAUCASICUM AND H. PASTINACIFOLIUM SUBSP. INCANUM ESSENTIAL OILS - Ozek, G.; Demirci, F.; Iscan, G.; Tabanca, N.; Wedge, D. E.; Duran, A.; Hamzaoglu, E.; Baser, K. H. C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
A study was conducted to evaluate the chemical composition and biological activities of Heracleum pastinacifolium C. Koch subsp. transcaucasicum (Manden.) Davis and H. pastinacifolium C. Koch subsp. incanum (Boiss. et Huet) Davis (Apiaceae) essential oils. Fruits and stems were separately subjected to hydrodistillation followed by simultaneous analysis by GC-FID and GC/MS. Fruit oil yields from each subspecies were 1.34% and 1.70%, respectively and stems from both subspecies produced very poor oil yields (0.03% and 0.04%, resp.). Fruit oils were found to be rich in esters (79% and 81%) with octyl acetate (35% and 5.6%), octyl butyrate (14% and 38%), and hexyl butyrate (8% and 30%) as major constituents of subsp. transcaucasicum and subsp. incanum, respectively. Over half of the stem oil of subsp. transcaucasicum was comprised fatty acids (53%) with hexadecanoic (27%), tetradecanoic (15%) and (Z)-9-hexadecenoic (11%) acids as main constituents. Phenylpropanoids (55%) with myristicin (50%) as the major compound comprised more than half of the stem oil of subsp. incanum. Fruit oils were subsequently investigated for antimicrobial, antifungal, antileishmanial, antimalarial, cytotoxic, and anticancer activities. Oils from both subspecies demonstrated weak antimicrobial activity in micro-dilution broth assays. Antileishmanial activity of the oil of subsp. incanum was determined to be IC50= 50 µg/mL and IC90= 90 µg/mL, while the oil of subsp. transcaucasicum was inactive towards leishmanial cells. There was no antimalarial activity or cytotoxicity against mammalian kidney fibroblasts (Vero). Oils were also ineffective against the plant pathogens Colletotrichum acutatum, C. fragariae and C. gloeosporioides tested by direct bioautographic assay.